THU0567 The Development of a Community Based Education/Self-Management Program for People with Ankylosing Spondylitis. (23rd January 2014) - Briffa, N. K.; Cook, N.; Edelman, J.; McQuade, J.
Abstract : Background: Whilst hospital based physiotherapy led education/exercise programs exist for ankylosing spondylitis (AS), there are few community based disease specific self management interventions Objectives: To develop a group education and self-management program, for adults with AS, promoting healthy lifestyles to optimise health outcomes. Using a continuous quality improvement collaborative approach, A scripted education program was developed utilising the Plan, Do, Study, Act (PDSA) model. Methods: 63 people (56% female), of mean (SD) age 46 (14.6) years, diagnosed with AS and 22 of their partners participated in nine sequential PDSA groups. Participant characteristics including AS specific quality of life (EASi-QoL); BASDI; BASFI; fatigue (FSS) health distress; and anxiety and depression (HAD) were measured 1 week before and 1 week after the program. 54 participants provided feedback post program using a questionnaire containing closed and open ended questions. Intervention One 2.5 hour group session facilitated by the same 2 health professionals was conducted weekly for 6 weeks. A 20 min tea break and intermittent stretch breaks were incorporated. Program content included self-management constructs, goal setting, problem solving, and behaviour management along with disease specific information on pathophysiology, medications, strategies to cope with depression, fatigue and pain, and the importance of exercise, stretching, posture and relaxation. Benefits of exercise were stressed but apart from stretches, supervised exercise was not part of the program. Results: 9 groups of 4 to 11 people participated in the program. PDSA quality improvement included increasing the number and duration of breaks for stretching and providing floor mats if a rest from sitting was required. "Ice breakers" were added to the first session. More information on working with AS, special diets for AS and complimentary therapies was requested and consequently expanded on for subsequent groups. Participants enjoyed the interaction and suggested 6/12 refresher sessions to keep their knowledge up to date. Participant characteristics did not change after the program (Table ). Feedback from the participants of all groups has been consistently positive with all participants saying they would recommend the program to others. Conclusions: The PDSA approach resulted in an Education/Self-Management program meeting the needs of people with AS. We intend to test this scripted program in a controlled trial to determine effectiveness. Disclosure of Interest: N. Briffa Grant/research support from: Program was developed using an educational grant from Arthritis Australia which included 'untied' sponsorship from AbbVie Pty Ltd, N. Cook Grant/research support from: Program was developed using an educational grant from Arthritis Australia which included 'untied' sponsorship from AbbVie Pty Ltd, J. Edelman Grant/research support from: Program was developed using an educational grant from Arthritis Australia which included 'untied' sponsorship from AbbVie Pty Ltd, J. McQuade Grant/research support from: Program was developed using an educational grant from Arthritis Australia which included 'untied' sponsorship from AbbVie Pty Ltd